The Study of Exposure to Occupational Carcinogens in Iran: A Scoping Review - Karimiyan, Mobina; Mohagheghi, Mohammad Ali; Fallahi, Majid; Saghi, Mohammad Hossien; Feizabadi, Mansoureh; Halimi, Aram; Khavari, Tina; Azizi, Fatemeh; Asadipour, Fatemeh; Hasanzadeh, Mohammad; et al. (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Occupational exposure to carcinogens is a significant issue in occupational health and public welfare, with carcinogens encompassing a wide range of substances such as chemicals, metals, dust particles, and organic materials. This scoping review aims to identify, map, and summarize the existing literature on occupational carcinogen exposure in Iran across various industries and settings. It categorizes the types of carcinogens investigated, evaluates the methodologies employed for exposure assessment, and identifies research gaps and areas needing further exploration. Methods: A systematic search was conducted across multiple databases including PubMed, Scopus, Web of Science, Scientific Information Database (SID), and Magiran. A total of 715 articles were identified, with inclusion criteria focusing on studies conducted in Iran, directly related to occupational carcinogen exposure, and available in full text in English or Persian. Title and abstract screening, followed by full-text evaluation, was performed by two independent reviewers. Key data were extracted and thematically analyzed to synthesize findings. Results: The review highlights prevalent types of occupational carcinogens studied in Iran and the industries that have been the primary focus of research. It discusses the various methodological approaches used to assess and quantify exposure levels, identifies key findings related to exposure and associated health risks, and uncovers significant gaps in the literature. Conclusion: This scoping review provides a nuanced portrait of occupational carcinogen exposure in Iran, identifying critical research gaps and offering a foundation for future studies. By consolidating existing knowledge, it aims to contribute to the enhancement of occupational health and safety practices in Iran, guiding the development of targeted interventions and regulatory policies.